“Misogyny Was in the Atmosphere”: Feminist Perspectives on Social Media Use in the 2019 Algerian Pro-Democratic Demonstrations - Rim H. Chaif; Christopher E. Etheridge (Social Media + Society)
Public and vocal calls by Algerian feminist groups to revise restrictive laws about women during the 2019 Hirak (“protest” in Arabic) were met with physical and online violence from both pro-government and reformist groups. Theories considering the role of public spaces in advancing democratic efforts differ on strategy and method for inclusion of marginalized voices. Through structured open-ended questionnaires with Algerian feminist demonstrators, this study probes the perceived efficacy of various democratic-advancing tactics. Findings show a reticence on the part of Algerian feminists in cultivating open social media spaces or efforts to assimilate into a single public and echo previous findings of those advocating for a more disputed perspective on democracy.